Commissioning of a proton gantry equipped with dual x‐ray imagers and a robotic patient positioner, and evaluation of the accuracy of single‐beam image registration for this system. Issue 6 (21st May 2015) - Wang, Ning; Ghebremedhin, Abiel; Patyal, Baldev
Abstract : Purpose: To check the accuracy of a gantry equipped with dual x‐ray imagers and a robotic patient positioner for proton radiotherapy, and to evaluate the accuracy and feasibility of single‐beam registration using the robotic positioner. Methods: One of the proton treatment rooms at their institution was upgraded to include a robotic patient positioner (couch) with 6 degrees of freedom and dual orthogonal kilovoltage x‐ray imaging panels. The wander of the proton beam central axis, the wander of the beamline, and the orthogonal image panel crosswires from the gantry isocenter were measured for different gantry angles. The couch movement accuracy and couch wander from the gantry isocenter were measured for couch loadings of 50–300 lb with couch rotations from 0° to ±90°. The combined accuracy of the gantry, couch, and imagers was checked using a custom‐made 30 × 30 × 30 cm 3 Styrofoam phantom with beekleys embedded in it. A treatment in this room can be set up and registered at a setup field location, then moved precisely to any other treatment location without requiring additional image registration. The accuracy of the single‐beam registration strategy was checked for treatments containing multiple beams with different combinations of gantry angles, couch yaws, and beam locations. Results: The proton beam central axis wander from the gantry isocenter was within 0.5 mm with gantry rotations in both clockwise (CW) and counterclockwise (CCW) directions. The maximum wander of the beamline and orthogonal imager crosswire centers from the gantry isocenter were within 0.5 and 0.8 mm, respectively, with the gantry rotations in CW and CCW directions. Vertical and horizontal couch wanders from the gantry isocenter were within 0.4 and 1.3 mm, respectively, for couch yaw from 0° to ±90°. For a treatment with multiple beams with different gantry angles, couch yaws, and beam locations, the measured displacements of treatment beam locations from the one based on the initial setup beam registered at the gantry at 0°/180° and couch yaw at 0° were within 1.5 mm in three translations and 0.5° in three rotations for a 200 lb couch loading. Conclusions: Results demonstrate that the gantry equipped with a robotic patient positioner and dual imaging panels satisfies treatment requirements for proton radiotherapy. The combined accuracy of the gantry, couch, and imagers allows a patient to be registered at one setup position and then moved precisely to another treatment position by commanding the robotic patient positioner and delivering treatment without requiring additional image registration.